A cross-sectional study on prevalence of substance use and its determinants among the male youth aged 15-24 years of slums of city Amritsar - Sharma, Sahil; Mahajan, Sanjeev; Lal, Mohan; Singh, Tejbir; Deepti, Shyam Sunder; Kaur, Jasleen (International Journal Of Community Medicine And Public Health, 2019)
Background: Slums are not new phenomenon. They are characterized by insanitary condition, crime, drug abuse etc. The male youth living in the slums, are prone to various health impacting conditions including substance use like alcohol consumption, smoking, tobacco chewing, drugs etc. Methods: Cross-sectional study was conducted in the four selected urban slums of Amritsar city. From each slum 250 male youth aged 15-24 years were included in the study, so total 1000 respondents were interviewed and required information was filled in pre-designed semi-structured proforma. Data was compiled, analysed and valid conclusions were drawn. Results: The overall prevalence of substance use among the respondents was 25.9% and as the age increases the prevalence of substance use also increases. Among substance users, tobacco (86.8%) was the most common substance consumed both in smoking form (52.1%) and smokeless form (34.7%), followed by the alcohol (72.2%) and then drugs (12%). Majority (62.1%) of respondents had initiated the substance use between 15-19 years of age. Factors like illiteracy, migration, joint family, married status and increased mental stress were significantly associated with substance use, however no association was found with socio economic status of the respondents. Conclusions: Government should take robust steps to improve the awareness and education status of the youth living in the slums. As the younger ages are most vulnerable ones, health education, IEC and BCC activities regarding the harmful effects of substance use along with life skills should be incorporated into the school curriculum.